Comparative Study of Cranial Measurement between Bengali and Manipuri Adult Male (Bangladesh Journal of Anatomy, 2021)
Background: Present research work focuses to identify the differences of cranial measurements among two ethnic groups, Bengali and Manipuri male, based on different cranial parameters. This study can provide the basic framework for formulating standards of the cranial dimensions and indices for Bengali and Manipuri male. Materials and methods: The study was cross sectional in nature with some analytical component, carried out in the Department of Anatomy, Chittagong Medical College, Chattogram, from July 2016 to June 2017. Two cranial variables were measured by physical procedure and one index was calculated from the measured values on 100 Bengali male and 100 Manipuri male, aged between18 to 50 years. All collecting data were analyzed by SPSS-20 using unpaired student ‘t’ test. Results: This study showed that mean maximum cranial length of Bengali and Manipuri were 19.09 ±1.05cm and 19.08 ±.92cm respectively; mean maximum cranial breadth were 15.08±.61cm and 15.82±.57cm respectively, and mean cephalic indices were 79.20 ± 4.64 and 83.01± 2.67 respectively. Bengali (44%) and Manipuri (42%) had very long type of head based on maximum cranial length. Based on maximum cranial breadth 71% of Bengali had medium head and 65% of Manipuri had broad type of head. Bengali had dolichocephalic (37%) and mesocephalic head (37%) whereas Manipuri had brachycephalic head (66%). Conclusion: This study provided some base line data for comparative evaluation of cranial measurements between Bengali and Manipuri adult male.Bangladesh Journal of Anatomy July 2021, Vol. 19, No. 2, pp. 43-48